Perception of bottlenecks in the implementation of the European Water Framework Directive - Zingraff-Hamed, Aude; Schroeter, Barbara; Bulian, Simon; Lepenies, Robert; Stein, Ulf; Hueesker, Frank; Meyer, Claus; Schleyer, Christian; Schmeier, Susanne; Pusch, Martin T. (Water alternatives, 2020)
The European Water Framework Directive (WFD) entered into force in December 2000; it marks a decisive turn in European water governance and related policies, management practices and restoration trends. After 20 years of implementation through two management cycles, EU member states have transposed the WFD requirements into national law, performed baseline assessments of water bodies, and implemented first measures such as hydromorphological river restoration which aims to achieve 'good ecological status', or at least the potential level targeted for that particular water body, by 2027. So far, however, WFD implementation has shown limited success; this weak result has given rise to studies, which are mainly discussions about possible technical limitations of WFD implementation and the appropriateness of monitoring procedures. This paper complements these studies by exploring governance-related bottlenecks that have emerged in the last two decades, as perceived by scientists and practitioners. An online survey was conducted which built on a list of 24 barriers to WFD implementation; these barriers had been identified previously by more than 40 researchers during a workshop in January 2019 and through a literature review. In this survey, the list of perceived barriers to WFD implementation was shared to 130 scientists and practitioners, who were asked to prioritise the items on list. Taken together, four main barriers to WFD implementation were identified: 1) problems related to horizontal intersectoral communication, 2) insufficient land reserves, 3) insufficient staff capacities, and 4) inadequate funding. The results of the analysis of WFD implementation indicated a bottleneck at the governance level that was due to insufficient horizontal collaboration and communication. This result is not in line with previous surveys that identified policy integration as the main bottleneck. We conclude from this that the governance dimension of WFD implementation merits more attention in terms of both research and political consultation in order to identify the needs for action that are key to improved WFD implementation.
Gesehen am 14.12.2020